Peran Teknologi dalam Mendukung Pendidikan Inklusif di Era Globalisasi: Kajian Filsafat Ilmu Pendidikan - Yonatan, Amandus; Radiana, Usman; Rommise, Wewel (Juwara: Jurnal Wawasan dan Aksara, 2024)
This research aims to analyze the role of technology in supporting inclusive education in the era of globalization from the perspective of philosophy of education. The focus of this research is to explore the philosophy of education perspective and how the role of technology can strengthen the principles of inclusive education, such as equality, fairness and accessibility for all learners, including those with special needs. The method used is a literature review with a qualitative approach, where sources from the philosophy of education, inclusion studies, and technological developments in education are reviewed in depth. This research also applies a critical analysis approach to evaluate the challenges and opportunities presented by technology in the context of inclusive education. The results show that technology has great potential to improve access and active participation in the learning process, especially through personalization and adaptation of learning materials. However, the research also found that there are risks of disparities in access to technology as well as ethical implications related to the use of technology that can reduce social interaction in the learning environment. Therefore, a holistic approach is needed in the implementation of technology that not only focuses on efficiency, but also on human values and social justice in education.